A new species of the ghost shrimp genus Lepidophthalmus (Crustacea: Decapoda: Axiidea) from the southwestern Gulf of Mexico - Felder, Darryl L. (Zootaxa, 2015)
A new species of Lepidophthalmus lacking a ventral median sclerite on the second abdominal somite is described from coastal waters of the southwestern Gulf of Mexico. Lepidophthalmus statoni sp. nov., originally recognized only as a unique population in allozyme studies, is sympatric with the ventrally plated species Lepidophthalmus manningi Felder & Staton, 2000, but more closely resembles Lepidophthalmus louisianensis (Schmitt, 1935) from the northern and northwestern Gulf of Mexico. Apparently restricted to intertidal and shallow subtidal tropical waters, the new species is known to range from western Campeche to middle-upper reaches of Veracruz, Mexico. As many members of the genus, it commonly inhabits euryhaline inlets, estuaries, and protected shorelines, including richly organic muddy to clayey sands and sandy muds adjacent to shoreline vegetation. Coloration is documented and discussed as a tool to facilitate field identifications, as are morphological characters.